Good Work, Secret Seven - Enid Blyton
Peter and Janet are the only witnesses when a car is stolen! They saw the thieves, and now the whole of the Secret Seven are involved. But when they realise they're on the trail of a dangerous gang, the Seven don't feel quite so brave. Have they taken on too much this time?